Pengaruh Inflasi, Jumlah Uang Beredar (JUB), Tingkat Suku Bunga SBI (BIRATE), dan Nilai Tukar (KURS) terhadap Indeks Harga Saham di Jakarta Islamic Index (JII) dan Index Liquid-45 (LQ-45) (Periode Januari 2006 - Desember 2014) - NAWANGWULAN, Nydia Elga Ayu; , Eni Setyowati, SE, M.Si; , Nurul Huda, S.Ag., M.Ag (2015)
Share price index can be regarded as a barometer of a country's economy and as a basis for statistical analysis of past market conditions. This study aims to determine how the effects of inflation, JUB, BIRATE, and EXCHANGE against sharia stock index contained in the JII and conventional stock price index contained in LQ-45 period January 2006 to December 2014 and how much influence a given variable The macroeconomic against sharia stock index contained in the JII and conventional stock price index contained in LQ-45. The method used in this research is descriptive and analytical, while the model used will be estimated by means of analysis Partial Adjustment Model (PAM) and Classical Assumption Test treated with Quantitative Micro Soffware E-Views version 7.0.0.1. The test results are expected to be used as consideration and reference for investors to invest in the stock market, particularly related to the level of selectivity in the choice of shares in accordance with sharia. The population in this study is a monthly report development of macroeconomic indicators and the closing price of the index JII and LQ-45. While the quarterly progress report of macroeconomic indicators and the closing share price from January 2006 to December 2014 chosen as the study sample. This is done because the monthly data obtained consideration totaling 108 months, in which the expected amount of it already meets the small sample size for the normal distribution of data. From the result of a partial adjustment data (PAM) have shown that the coefficient of inaction JII dependent variable and the LQ-45 is compliant, and it means that the model is actually a model of PAM. Classical assumption test was conducted on the model passed all except multicolinearity test. At JUB variables found a problem multicollinearity, since it is known the value VIFnya figures show more than 10 percent, which is 14.82 percent and 15.99 percent for JII for LQ-45. But this should not be a significant problem in this study. Found there are two macroeconomic variables that significantly influence the stock price index JII and LQ-45, that inflation has a significant negative influence and JUB which has a significant positive effect. What distinguishes the two is both the macroeconomic variables affect the larger of the LQ-45 than JII. Therefore, an investor should consider the information about inflation, JUB, BIRATE, and KURS to predict stock price index contained in the BEI especially JII and LQ-45 before making any decisions with respect to investments.